Enduring a five-set singles match (& the next match): physiology of preparation, competition & recovery - Christmass, M. (coachesinfo.com)
Successfully enduring a 5-set tennis match demands a sustained high level of technical, tactical, physiological and psychological capacity in often hostile environmental conditions. In terms of physiology, success is likely to depend on the player's ability to repeatedly generate power for explosive stroke production and for rapid court movement during extended matches. This paper outlines the effect of metabolic factors, and of playing in hot environments, on fatigue and tennis performance as well as physiological preparation to minimise these effects. Fitness training, nutrition and hydration are discussed and strategies are presented to help sustain physiological performance during a match and to optimise preparation for the next match. This paper discusses the scientific background to physiological performance in tennis and in particular the effect of metabolic factors, and of hot environments, on fatigue in tennis. Scientific findings are presented as the basis for recommendations on fitness training, nutrition and hydration to help players prepare and compete in extended matches and to recover during tournament competition. In each case scientific background is followed by a summary of specific recommendations for coaches and players. Summary & Conclusion : Fatigue impairs tennis stroke production and court movement and hence improving physiological performance is likely to benefit players. In terms of physiological performance, successfully enduring a 5-set (i.e. long) tennis match is likely to depend in part on the capacity to repeatedly generate power across several hours of play. Fitness training for tennis should focus on developing the phosphocreatine energy system (i.e. various forms of training for power). But a high level of aerobic fitness is also crucial to facilitate recovery between rallies and to a lesser extent to improve tolerance of hot conditions in non-acclimated players. Hot environments and dehydration impair physical and mental performance variables relevant to tennis. Where necessary, players should acclimatise by training daily for 6-8 days in the hot environment. Pre-match dietary carbohydrate intake to maintain glycogen stores is important but dehydration may cause fatigue before glycogen stores are depleted. Carbohydrate drinks during competition may improve physiological performance and will also contribute to delaying fatigue due to dehydration. Recent evidence indicates that carbohydrate-electrolyte drinks may improve tennis-specific performance. For long matches (3 h) players should consume 800-1600 ml.h-1 of a 6-8% carbohydrate solution containing 10-20 mM sodium (this volume range is large and specific intake will depend on individual sweat rate and environmental conditions). For effective post-match recovery players should begin consumption of carbohydrate (50 g.2 h-1, total > 600 g for 70 kg body mass) and fluid (sodium content 50 mM; 1.5-2.0-fold the exercise fluid loss) as soon as possible after the match.